2001
DOI: 10.1046/j.1432-1327.2001.02295.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐clustering of Fcγ and B cell receptors induces dephosphorylation of the Grb2‐associated binder 1 docking protein

Abstract: The immunoreceptor tyrosine-based inhibitory motif (ITIM) of human type IIb Fcg receptor (FcgRIIb) is phosphorylated on its tyrosine upon co-clustering with the B cell receptor (BCR). The phosphorylated ITIM (p-ITIM) binds to the SH2 domains of polyphosphoinositol 5-phosphatase (SHIP) and the tyrosine phosphatase, SHP-2. We investigated the involvement of the molecular complex composed of the phosphorylated SHIP and FcgRIIb in the activation of SHP-2. As a model compound, we synthesized a bisphosphopeptide, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 42 publications
3
32
0
Order By: Relevance
“…23 SHIP also has been shown to recruit p62Dok and to modulate Ras activity and also may induce the activation of SHP2. 24,25 Our in vitro and in vivo findings suggest that the increased rate of BMMC maturation and tissue mast cell numbers because of SHIP deficiency are predominantly a result of enhanced PI3K activity via the recruitment and activation of the p85␣-p110 PI3K complex, because deficiency of p85␣ alone in BMMCs lacking SHIP corrects the enhanced maturation defect in vitro and partially restores normal mast cell numbers in vivo. These findings are further supported by conducting experiments using WT and p85␣ Ϫ/Ϫ MCps expressing activated versions of PI3K and AKT, respectively.…”
Section: Discussionmentioning
confidence: 80%
“…23 SHIP also has been shown to recruit p62Dok and to modulate Ras activity and also may induce the activation of SHP2. 24,25 Our in vitro and in vivo findings suggest that the increased rate of BMMC maturation and tissue mast cell numbers because of SHIP deficiency are predominantly a result of enhanced PI3K activity via the recruitment and activation of the p85␣-p110 PI3K complex, because deficiency of p85␣ alone in BMMCs lacking SHIP corrects the enhanced maturation defect in vitro and partially restores normal mast cell numbers in vivo. These findings are further supported by conducting experiments using WT and p85␣ Ϫ/Ϫ MCps expressing activated versions of PI3K and AKT, respectively.…”
Section: Discussionmentioning
confidence: 80%
“…T cells expressing a phophataseinactive SHP-2 variant develop normally but generate enhanced immune responses. It has been shown previously that FcγRIIb co-engagement with the BCR leads to dephosphorylation of CD19 and Gab-2 [39,40]. An increased integration of SHP-2 might be the explanation for this observation.…”
Section: Discussionmentioning
confidence: 58%
“…1c). Our earlier peptide pull-down experiments followed by Western blot revealed that the major molecule interacting both with pITIM, the chimera and GD-LD PPs was SHP-2 [15,39] indicating that these PPs may regulate the activity of SHP-2 phosphatase ex vivo.…”
Section: Resultsmentioning
confidence: 96%
“…SHP-2 is activated by the simultaneous engagement of its two SH2 domains by a bisphosphorylated activation motif [2,38]. Accordingly, we also tested the effects of a chimeric bisphosphorylated peptide consisting of pITIM and a phosphotyrosine-containing peptide of SHIP combined with a flexible linker [TEIINPNY(p)MGVG(AG) 15 AENTITY(p)SLLMHP, chimera] [39]. This chimeric peptide induced the tyrosine phosphorylation of proteins at 30, 50 and 66-70 kDa in a dose-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 99%